Peran Penyuluhan Agama dalam Meningkatkan Integritas Keagamaan Remaja - Putri Adeyola, Aisyah; Nur’aini, Dika; Junia Vitaloka, Viola; Widyawanti Wati, Nuraifah; Slamet Riyadi (Yayasan Darussalam Bengkulu, 2023)
The aim of this research is to determine the duties and roles of religious counselors in improving the religious integrity of adolescents. This research was conducted in Bengkulu City, where in this area there is still a lack of religious integrity among teenagers. The data collection technique was carried out using the literature review research method. The author looked for data and materials, references from journals and articles, as well as references from books to serve as a strong basis for the content and arguments.The aim of this research is to determine the duties and roles of religious counselors in improving the religious integrity of adolescents. This research was conducted in Bengkulu City, where in this area there is still a lack of religious integrity among teenagers. The data collection technique was carried out using the literature review research method. The author looked for data and materials, references from journals and articles, as well as references from books to serve as a strong basis for the content and arguments.